2020
DOI: 10.1093/infdis/jiaa623
|View full text |Cite
|
Sign up to set email alerts
|

A Dual-Antigen Enzyme-Linked Immunosorbent Assay Allows the Assessment of Severe Acute Respiratory Syndrome Coronavirus 2 Antibody Seroprevalence in a Low-Transmission Setting

Abstract: Estimates of seroprevalence of SARS-CoV-2 antibodies have been hampered by inadequate assay sensitivity and specificity. Using an ELISA-based approach that combines data about IgG responses to both the Nucleocapsid and Spike-receptor binding domain antigens, we show that excellent sensitivity and specificity can be achieved. We used this assay to assess the frequency of virus-specific antibodies in a cohort of elective surgery patients in Australia and estimated seroprevalence in Australia to be 0.28% (0 to 1.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
3
12
1
Order By: Relevance
“…We noted however, that the 13 participants in this study previously diagnosed with COVID-19 represented 21% of known EH HCW infections, whereas only seven percent of the overall workforce participated in our study. Our work mirrors a previous a sero-surveillance study of the general population in Australia and international studies which indicate that a significant proportion of infections are being missed by symptomatic or directed testing ( 7 , 13 , 14 ). Despite this, our study only identified three HCW with positive serology who had not previously been diagnosed by PCR testing.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We noted however, that the 13 participants in this study previously diagnosed with COVID-19 represented 21% of known EH HCW infections, whereas only seven percent of the overall workforce participated in our study. Our work mirrors a previous a sero-surveillance study of the general population in Australia and international studies which indicate that a significant proportion of infections are being missed by symptomatic or directed testing ( 7 , 13 , 14 ). Despite this, our study only identified three HCW with positive serology who had not previously been diagnosed by PCR testing.…”
Section: Discussionsupporting
confidence: 86%
“…Based on this sample, we determined the seroprevalence of SARS-CoV-2 antibodies in healthcare workers at Eastern Health to be 2.17%. This was higher than previous estimates of seroprevalence in the Australian community, which ranged from 0.15% to 0.79% ( 7 , 8 ), however, these figures, calculated from samples collected prior to the second wave of infections, likely underestimate community seroprevalence.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…However, even with robust testing many cases will be undiagnosed, especially asymptomatic cases, which could constitute half of all infections [30]. A recent seroprevalence study of elective surgery patients in four states [31] estimated that the number of true infections was around 5-10 times the number of reported cases, although the authors state that the study cohort may not reflect the general population (older individuals overrepresented). This prevalence ratio gives an approximate IFR for Australia of 0.1-0.3%.…”
Section: Discussionmentioning
confidence: 99%
“…However, even with robust testing, many cases will be undiagnosed, especially asymptomatic cases, which could constitute half of all infections [ 35 ]. A recent seroprevalence study of elective surgery patients in four states [ 36 ] estimated that the number of true infections was around 5–10 times the number of reported cases, although the authors state that the study cohort may not reflect the general population (older individuals overrepresented). This prevalence ratio gives an approximate IFR for Australia of 0.1–0.3%.…”
Section: Estimating the Infection Fatality Ratio From The Cfrmentioning
confidence: 99%